2004
DOI: 10.1111/j.1365-2265.2004.02030.x
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Chromogranin A for diagnosis and follow‐up of endocrine tumours

Abstract: Due to its high specificity, CgA determination may help to discriminate the endocrine character of a GEP tumour and to indicate a pancreatic tumour in MEN-1. However, its low NPV in nonsecreting tumours limits its interest for diagnosis and staging. By contrast, serial evaluation of CgA seems of particular interest for the follow-up of GEP-ET tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
112
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 38 publications
14
112
1
1
Order By: Relevance
“…A különböző endokrin szö-vetekben proteolitikus módosításokat követően alakul át extracellulárisan működő biológiailag aktív peptidformákká. A CgA-ból kialakuló fehérjék, mint a pancreastatin, a vasostatin, a WE-14 és további formák jelentős és specifi kus biológiai hatással rendelkeznek (1. táblázat) [26,27,28,29,30,34,35,45,47,48,49,50,51,52].…”
Section: Következtetésekunclassified
“…A különböző endokrin szö-vetekben proteolitikus módosításokat követően alakul át extracellulárisan működő biológiailag aktív peptidformákká. A CgA-ból kialakuló fehérjék, mint a pancreastatin, a vasostatin, a WE-14 és további formák jelentős és specifi kus biológiai hatással rendelkeznek (1. táblázat) [26,27,28,29,30,34,35,45,47,48,49,50,51,52].…”
Section: Következtetésekunclassified
“…Recent studies confirmed that the measurement of CgA levels in blood can also be used to diagnose and to monitor neuroendocrine tumours during treatment [6,10,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 92%
“…In every case of diagnosed NET determination of CgA concentration has a significant impact on the prognosis and the choice of treatment and clinical outcome. Prognosis for the patients with NET secreting CgA is better, having a longer survival time and a prolonged time to progression [5,10,18,22,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated with long-term histamine type 2 receptor antagonists or proton pump inhibitors also have raised circulating CgA. 86,87 Because of all these, gastric hypochlorhydric and achlorhydric states are common; care must be taken in the interpretation of CgA results. A circulating CgA concentration of more than twice the reference range is usually indicative of NET, whereas concentrations lower than this are inconclusive.…”
Section: Chromogranin Bmentioning
confidence: 99%